Large-Scale Single-Cell and Bulk Sequencing Analyses Reveal the Prognostic Value and Immune Aspects of CD147 in Pan-Cancer - Zhang, Jingwei; Wang, Zeyu; Zhang, Xun; Dai, Ziyu; Zhi-Peng, Wen; Yu, Jing; Peng, Yun; Wu, Wantao; Zhang, Nan; Luo, Peng; Zhang, Jian; Liu, Zaoqu; et al. (Frontiers in Immunology, 2022)
CD147 plays an important role in promoting tumor proliferation and inhibiting cancer cell apoptosis in the tumor microenvironment. However, the mechanisms by which CD147 is involved in tumorigenesis in pan-cancer remains largely unclear. This study systematically analyzed the prognostic value and immune characteristics of CD147 in 32 cancer types. The expression levels and mutant landscapes of CD147 in pan-cancer were explored. The Kaplan-Meier (KM) analysis was applied to analyze the prognostic value of CD147 in 32 cancer types. The immune characteristics of CD147 in the tumor microenvironment were evaluated via TIMER 2.0 and R package (immunedeconv). We also explored the expression of CD147 on tumor cells and stromal cells through Gene Set Variation Analysis and single-cell sequencing analysis. The co-expression of CD147 and macrophage markers CD68, CD163 in pan-cancer was detected using multiplex immunofluorescence staining on tissue microarrays. CD147 was found to be overexpressed in almost all cancer types. Elevated CD147 levels were related to poor outcomes and were considered a promising prognostic marker in many cancer types. CD147 expression exhibited a close association with immune infiltrates, immune checkpoint molecules, and neoantigens levels in the tumor microenvironment. In addition, CD147 was expressed on various cell types in the tumor microenvironment, including tumor cells, macrophages, T cells, monocytes, fibroblasts, etc. Furthermore, immunofluorescence revealed the co-expression pattern of CD147 and macrophage markers CD68, CD163 in many tumor types. Finally, the immunotherapy response and sensitive small molecule drugs based on CD147 expression were predicted. CD147 has a significant relationship with the clinical outcome and immune infiltrates in multiple cancer types. Inhibiting the CD147-dependent signaling pathways might be a promising therapeutic strategy for tumor immunotherapy.